Metode Riset Kualitatif Yang Dapat Diandalkan untuk Mendukung Pengembangan Pelayanan Gereja dan Misinya - Harjanto, Sutrisna (Sekolah Tinggi Teologi Simpson Ungaran, 2024)
In recent decades, the use of qualitative research in Christian education and practical theology has experienced a remarkable surge. However, despite its growing acceptance, doubts persist regarding its reliability, fueled by numerous inadequately conducted studies and a lack of clarity surrounding its methodology. This article aims to dispel such skepticism by asserting the credibility of qualitative research methods. Through a systematic review of reputable literature, it reaffirms the fundamental characteristics of qualitative research, elucidates the factors contributing to its credibility, and underscores the significance of employing basic yet dependable methods. By adhering to these principles and fostering the development of robust basic qualitative research, the article contends that qualitative research has the potential to greatly enhance the advancement of church ministry and mission endeavors in Indonesia.